Slow-Speed Compared With Fast-Speed Eccentric Muscle Actions Are Detrimental to Jump Performance in Elite Soccer Players In-Season - Mark Waldron (International Journal of Sports Physiology and Performance, 2022)
Purpose: To examine the effect of fast-speed vs. slow-speed eccentric muscle actions resistance training on lower-body strength, vertical jump height, sprint speed and COD performance in elite soccer players during a competitive season.Methods: Twenty-two elite soccer players, from a single team, were randomly selected to groups that undertook either 1 s (fast speed [1S]) or 4 s (slow speed [4S]) eccentric resistance training during the in-season period. A five-week programme was conducted during an elite top division European League soccer season. Performance measures, including predicted one repetition maximum (1RM) back squat, countermovement jump (CMJ), 20m sprint and change of direction (COD) were tested before and after the intervention period. Total match and training running distance and muscle soreness were also recorded during each week of the intervention.Results: An ANCOVA showed significant group effects (P = 0.01) for CMJ with a greater jump height in the 1S group post-intervention (95% CI [1.1 to 6.9 cm]). Despite an overall increase in 1RM pre- to post-training (95% CI [10.0 kg to 15.3 Kg], ES: 0.69), there were no significant differences (P > 0.05) between groups after the intervention. Similarly, there were no differences between groups for COD, 20 m sprint or muscle soreness.Conclusion: Faster eccentric muscle actions may be superior for increasing jumping movements in elite soccer players in-season.